Karakter Religius dalam Pendidikan Agama Katolik: Studi Persepsi Siswa tentang Hidup Beragama dalam Keragaman - Siswantara, Yusuf; Satya Bhakti, Angga; Indah Setiawati , Ludovica Dewi; Subowo, FX Bambang K (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
Diversity requires an attitude of respect. However, formalism removes respect by reinforcing religion as a social identity that often causes social unrest and unrest, in discrimination or religious conflicts. In itself, religion is 'not wrong', but it is often blamed for its existence ability as an identity capable of driving social dynamics, in particular social conflicts. Because of its potential conflict, many discussions associate religious formalism with factors of religious emotion or sensitivity, the purpose of the organization in the name of religion, or its role in the conflict, as well as character education for the sake of the nation. Unlike previous research, this study wanted to look at religion and formalism in the perception of religious life and its influence on religious education. Given the focus on perceptions and excavations of religious life, a mixed methodology approach is a design choice in this study. The study conducted a survey of respondents' perceptions and views on four approaches to religious life. The data was collected, managed with the help of the application, as well as analyzed together with interview data against a sample of respondents. The results of the analysis are narrated discriptively in 4 topics: the view of life of faith in four approaches, exploring the richness of faith as a unique religion, the potential relativism of truth, the meaning of critical power. All of these topics have an impact on Catholic education and are an evaluation of educational political policies in managing religion in developing religious character.